Odpowiedzi

Najlepsza Odpowiedź!
2009-11-22T17:25:38+01:00
A) 2x - 6 -5x > 3 - 2x -10
2x - 5x + 2x > 3 - 10 +6
-x > -1 /: (-1)
x < 1

Odwracamy znak nierownosci ponieważ dzielimy przez liczbe ujemna .

b) 3x + 1 -x + 3/4 >_ 4x - 2 /*4
12x + 4 -4x + 3 >_ 16x - 8
12x - 4x - 16x >_ -8 - 4 - 3
- 8x >_ -15 /: (-8)
x _< 15/8

c) x2 + 3x - 3x -9 > x2 - 2x + 2x - 4
x2 - 9 > x2 - 4
x2 - x2 > -4 + 9
0 > 5
2009-11-22T17:26:37+01:00
A
2x - 6 - 5x > 3 - 2x - 10
2x - 5x + 2x > 3 + 6 - 10
- x > - 1
x < 1
b
3x + 1 - x + 3/4 ≥ 4x - 2 mnożymy wszystko przez 4
12x + 4 - 4x + 3 ≥ 16x - 8
12x - 4x - 16x ≥ - 8 - 4 - 3
12x - 20x ≥ - 15
- 8x ≥ - 15
x ≤ 15/8
c
x² - 6x + 9 > x² - 4 - 1,5x + 4
x² - x² - 6x + 1,5x > - 9
- 4,5x > - 9
x < 9/4,5
x < 2
2009-11-22T17:52:51+01:00
A) 2(x-3)-5x > 3-2(x+5)
2x-6-5x>3-2x-10
2x-5x+2x>3-10+6
-x>-1 /:(-1)
x<1

b) 3x+1- x+3/4 ≥ 4x-2
3x-x-4x≥-2-¾-1
-2x≥-3¾ /:(-2)
x≤1,875

c) (x-3)² > (x+2)(x-2)- (1,5x -4)
x²-6x+9>x²-4-1,5x+4
x²-x²-6x+1,5x>-4+4-9
-4,5x>-9 /:(-4,5)
x<2